Multiscale methods in computational mechanics progress and accomplishments - Borst, René de; Ramm, E. (Ekkehard) 1940- (Lecture notes in applied and computational mechanics, 2011)
Many features in the behaviour of structures, materials and flows are caused by phenomena that occur at one to several scales below common levels of observation. Multiscale methods account for this scale dependence: They either derive properties at the level of observation by repeated numerical homogenization of more fundamental physical properties defined several scales below (upscaling), or they devise concurrent schemes where those parts of the domain that are of interest are computed with a higher resolution than parts that are of less interest or where the solution is varying only slowly. This work is a result of a sustained German-Dutch cooperation and written by internationally leading experts in the field and gives a modern, up-to-date account of recent developments in computational multiscale mechanics. Both upscaling and concurrent computing methodologies are addressed for a range of application areas in computational solid and fluid mechanics: Scale transitions in materials, turbulence in fluid-structure interaction problems, multiscale/multilevel optimization, multiscale poromechanics.